A SYSTEM APPROACH TO ASSESSMENT AND GOAL SETTING WITHIN ENERGY SECURITY SPHERE - Sukhodolia, Oleksandr (Стратегічна панорама, 2019)
In the paper are explored the problems of energy security description (as an object of control and regulation) as well as assessment parameters definition. The review of the existing theoretical approaches to the description of energy security is conducted; the modern tendencies of the development of theoretical models in this field are shown. The evolution of the development of conceptual approaches to the study of energy security has been supplemented by projecting transition to an open interacting systems (ecosystems) concept. There is proposed the new model for energy security description, based on systematic approach methodology. There have been proposed the approach to designate a set of parameters for energy security assessment which reflects «integrity», «structure», «functions», «relationships», «processes», «material» of the system. The proposed approach to description of a country’s energy security provides an option to assess the state (as a set of static parameters that reflect the perception of the system by external observer) and the ability of the system to develop and respond to threats (as a set of indicators that reflect the functions and processes within the system). Emphasis is made on the need to separate a goal setting in energy security (as an object of control and regulation) as a process and stage of strategic planning procedure within the national security framework. The importance of taking into account the subject’s outlook (public management values that reflect the political and economic model of governance) in the process of goal setting was emphasized. The model of subjectivism reduction in goal setting is proposed, due to the incorporation of the energy security system into the larger system.